World Development (Oxford Elsevier Science, 1995)
World Development is a multi-disciplinary monthly journal of development studies. It seeks to explore ways of improving standards of living, and the human condition generally, by examining potential solutions to problems such as: poverty, unemployment, malnutrition, disease, lack of shelter, environmental degradation, inadequate scientific and technological resources, trade and payments imbalances, international debt, gender and ethnic discrimination, militarism and civil conflict, and lack of popular participation in economic and political life. Contributions offer constructive ideas and analysis, and highlight the lessons to be learned from the experiences of different nations, societies, and economies. World Development recognizes 'development' as a process of change involving nations, economies, political alliances, institutions, groups, and individuals. Development processes occur in different ways and at all levels: inside the family, the firm and the farm; locally, provincially, nationally, and globally.
World Development is published monthly. Last issue received vol. 28 (2000) # 2
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; ECONOMIC LIFE; POLITICAL LIFE; PERIODICALS